Analisis Interdependensi Asimetri Hilirisasi Nikel Indonesia-Tiongkok - Iras Abyan Nugroho; Reza Triarda (Universitas Wahid Hasyim Semarang, 2026)
The industrial growth of the nickel sector has begun to play a significant impact in the current global economy and politics, particularly in the green energy and manufacturing sectors. As the largest nickel reserve holder, Indonesia has implemented a downstreaming policy aimed at increasing added value, attracting foreign investment, and strengthening its global economic position. With China as a significant player as a buyer, investor, and technology provider, the economic interdependence between the two countries remains unbalanced. Using Keohane and Nye's asymmetric interdependence framework, this study highlights sensitivity interdependence and vulnerability interdependence through policy analysis and qualitative data. The findings indicate that China is more sensitive to Indonesia's downstreaming policy, while Indonesia is more vulnerable to China’s investment and technology. These findings demonstrate a mutually beneficial yet unequal relationship in the economic cooperation interdependence between the two countries.